The Campaign for Representative Government in Newfoundland - Bannister, Jerry (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 1994)
AbstractThis paper examines the campaign for an elected assembly in Newfoundland, granted in 1832, and challenges established views of the Colony's reform movement. In the early nineteenth century reformers repeatedly appealed for a local legislature, but their efforts met with limited success in the face of opposition from both merchants and government officials. However, fuelled by concerns over taxation, the reform movement transformed in 1828 into a viable coalition for representative government. In London the reformers overcame the government's intransigence through a strategy designed to gain support in Parliament and to undermine the Colonial Office. An analysis of the rhetoric employed in local meetings and petitions, as well as in Parliamentary debates, suggests that an assertive press and an inclusive public discourse played crucial roles in the reform movement's ability to embrace disparate socio-economic interests.